Genome-wide analysis of the chromatin sites targeted by HEX 70a storage protein in the honeybee brain and fat body - Martins, Juliana R.; Pinheiro, Daniel G. [UNESP]; Ahmed, Amy C. C.; Giuliatti, Silvana; Mizzen, Craig A.; Bitondi, Márcia M. G. (Wiley, 2023)
Hexamerins, the proteins massively stored in the larval haemolymph of insects, are gradually used throughout metamorphosis as a source of raw material and energy for the development of adult tissues. Such behaviour defined hexamerins as storage proteins. Immunofluorescence experiments coupled with confocal microscopy show a hexamerin, HEX 70a, in the nucleus of the brain and fat body cells from honeybee workers, an unexpected localization for a storage protein. HEX 70a colocalizes with fibrillarin, a nucleolar-specific protein and H3 histone, thus suggesting a potential role as a chromatin-binding protein. This was investigated through chromatin immunoprecipitation and high-throughput DNA sequencing (ChIP-seq). The significant HEX 70a-DNA binding sites were mainly localized at the intergenic, promoter and intronic regions. HEX 70a targeted DNA stretches mapped to the genomic regions encompassing genes with relevant functional attributes. Several HEX 70a targeted genes were associated with H3K27ac or/and H3K27me3, known as active and repressive histone marks. Brain and fat body tissues shared a fraction of the HEX 70 targeted genes, and tissue-specific targets were also detected. The presence of overrepresented DNA motifs in the binding sites is consistent with specific HEX 70a-chromatin association. In addition, a search for HEX 70a targets in RNA-seq public libraries of fat bodies from nurses and foragers revealed differentially expressed targets displaying hex 70a-correlated developmental expression, thus supporting a regulatory activity for HEX 70a. Our results support the premise that HEX 70a is a moonlighting protein that binds chromatin and has roles in the brain and fat body cell nuclei, apart from its canonical role as a storage protein.
Keywords: Apis mellifera; ChIP-seq; HEX 70a; hexamerin; nuclear protein; storage protein